2017
DOI: 10.1097/qai.0000000000001204
|View full text |Cite
|
Sign up to set email alerts
|

Development of a National Campaign Addressing South African Men's Fears About HIV Counseling and Testing and Antiretroviral Treatment

Abstract: Introduction:South African men are less likely to get tested for HIV than women and are more likely to commence antiretroviral treatment (ART) at later stages of disease, default on treatment, and to die from AIDS compared with women. The purpose of this study was to conduct formative research into the ideational and behavioral factors that enable or create obstacles to mens' uptake of HIV counseling and testing (HCT) and ART. The study consulted men with a goal of developing a communication campaign aimed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 11 publications
5
22
0
Order By: Relevance
“…In the era of treatment as prevention, more efforts are needed to develop and implement strategies to increase linkage to care among men in sub-Saharan Africa such as the effort to develop a national campaign to address men’s fear about HIV testing and treatment in South Africa [ 54 ]. For self-testers in particular, home-based confirmatory HIV testing and treatment has been found to increase linkage to care compared to facility confirmatory HIV testing in Malawi [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the era of treatment as prevention, more efforts are needed to develop and implement strategies to increase linkage to care among men in sub-Saharan Africa such as the effort to develop a national campaign to address men’s fear about HIV testing and treatment in South Africa [ 54 ]. For self-testers in particular, home-based confirmatory HIV testing and treatment has been found to increase linkage to care compared to facility confirmatory HIV testing in Malawi [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The tendency for men in sub-Saharan Africa to delay HIV testing and initiating treatment until their health deteriorates has been well described ( Mburu et al, 2014 ; Nyamhanga, Muhondwa, & Shayo, 2013 ; Skovdal et al, 2011 ). The delay in testing and eventual HIV status disclosure is due to HIV stigma and the fear of a potential HIV diagnosis, which can negativelly affect masculine pride and reputation ( Iwelunmor, Sofolahan-Oladeinde, & Airhihenbuwa, 2015 ; Mburu et al, 2014 ; Orr et al, 2017 ; Siu et al, 2013 ; Skovdal et al, 2011 ). However, the finding that men are learning from the experiences of their HIV-positive friends who tested late to encourage their peers to test for HIV and access treatment is less discussed in the literature and warrants further research.…”
Section: Discussionmentioning
confidence: 99%
“…Messages about HIV testing and ART need to target men and address their specific needs and concerns in places where men feel comfortable [ 19 ]. Previous research has indicated men’s interest in receiving information in a male dominated environment, from male HCWs, in the privacy of their homes and through information directed at them (not via their partners) [ 17 , 18 , 38 ].…”
Section: Discussionmentioning
confidence: 99%